Implementation of Hybrid Work System in Supporting Employees’ Work-Life Balance - Sidik, Irfan Maulana; Firmansyah, Yayan; Mukaram; Ciptagustia, Annisa (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
This study aims to determine the results of descriptive analysis of each variable and also the imfact of the effectiveness of the hybrid work system in supporting employee work-life balance at PT Senang Ganyang Lapar. The quantitative causality method is the method used in this research. Data collection techniques using questionnaires to employees at PT Senang Ganyang Lapar. The technique used for sampling in this study is the census sampling technique. The data analysis method used in this study uses SmartPLS software by conducting validity, reliability and hypothesis testing. The result of this study shows that hybrid working has a positive and significant influence on employee work-life balance at PT Senang Ganyang Lapar.